Fullerene and bismuth clusters on nanostructured oxide films - Kononov, Alexander (Technische Universität Dortmund, 2024)
In this study, C60 molecules and Bi clusters are investigated on the surfaces of two noble metals (Au(111) and Ag(111)) and on the surface of Al2O3||Ni3Al, characterized by very low conductivity. For the investigation, ultraviolet photoelectron spectroscopy (UPS) and scanning tunneling microscope (STM) are used in ultra-high vacuum (UHV). On the Al2O3||Ni3Al surface, both C60 and Bi clusters exhibit a noticeable shift of the photoemission signal due to the influence of the charging energy: in the case of C60, this shift is attributed to the energy shift of the HOMO, while for Bi clusters, it is visible for the shift of the core level. Conversely, minimal shifts is observed on metal surfaces. For C60, the shift originates from the reduction in charging energy induced by next-neighbor screening, whereas for Bi clusters, it is attributed to the increase in cluster size, with the influence of the Ni3Al(111) surface playing a significant role in the change of core level shift. Both effects are explained within the electrostatic approximation, which overlooks quantum mechanical effects like local electron density distribution or electron spill-out, yet still yields excellent agreement with experimental results. Furthermore, STM investigations reveal evidence of Bi cluster adsorption on the periodic superstructure of the Al2O3||Ni3Al surface, and potentially even adsorption of C60 molecules on the periodic structure of the Al2O3||Ni3Al network.

In der vorliegenden Arbeit werden C60-Moleküle und Bi-Cluster auf den Oberflächen von zwei Edel- metallen (Au(111) and Ag(111)) sowie auf der Oberfläche von Al2O3||Ni3Al, das durch sehr niedrige Leitfähigkeit gekennzeichnet ist, untersucht. Zur Untersuchung werden Ultraviolettphotoelektronen- spektroskop (UPS) und Rastertunnelmikroskop (RTM) in Ultrahochvakuum (UHV) eingesetzt. Auf der Al2O3||Ni3Al-Oberfläche zeigen sowohl C60-Moleküle als auch Bi-Cluster eine deutliche Verschiebung des Photoemissionssignals aufgrund des Einflusses der Ladungsenergie: Im Fall von C60 werden dieser Effekt der Verschiebung des Energieniveaus des highest occupied molecular orbital (HOMO) zugeschrieben, während bei Bi-Clustern die Verschiebung des Kernniveaus beobachtet wird. Im Gegen- satz dazu werden auf Metalloberflächen nur minimale Verschiebungen festgestellt. Für C60 resultiert die Verschiebung aus der Reduktion der Ladungsenergie, die durch die Abschirmung durch Nachbarn hervorgerufen wird, während sie bei Bi-Clustern auf die Zunahme der Clustergröße zurückzuführen ist, wobei der Einfluss der Ni3Al(111)-Oberfläche eine bedeutende Rolle bei der Veränderung des Photoe- missionssignals des Kernniveaus spielt. Beide Effekte können innerhalb der elektrostatischen Näherung erklärt werden. Dabei werden die quantenmechanische Effekte wie lokale Elektronendichteverteilung oder der Elektron spill-out außer Achtgelassen. Dennoch zeigt diese Näherung eine ausgezeichnete Übereinstimmung mit den experimentellenErgebnissen. Darüber hinaus zeigen STM-Untersuchungen Hinweise auf die Adsorption von Bi-Clustern auf der periodischen Superstruktur der Al2O3||Ni3Al- Oberfläche und möglicherweise sogar die Adsorption von C60-Molekülen auf der periodischen Struktur des Al2O3||Ni3Al-Netzwerks.
Influence of nearest neighbors and surface contribution on charging energy
Keywords: PhD; Physics; STM; UPS; Oxides; Metals; Nanotechnoloy; Clusters; Surface; Fulleren; C60; Charging energy; uhv; ultra high vacuum; 530; Fullerene; Bismut; Atomcluster